Geoprocessamento aplicado a determinação de parâmetros hidrológicos de bacias hidrográficas - Camacho, Carlos Hugo Campos (2018)
The use of Geographic Information Systems (GIS), for the determination of the parameters has risen steadily over the past three decades. The availability of databases in Brazil through public institutions allows for an improvement in the process of parameterization of the Hydrographic Basin. In this work, a methodology for automating the use of pre-processed, calibrated and provided by the Public Agencies in Brazil and the use of these resources to combine them with free data provided by foreign environmental management institutions. It will be presented a computational tool in Python Script for use in Geoprocessing in the ArcGIS program and the result will be the morphological parameters of a hydrographic basin for its use in hydrological-hydraulic modeling in several Software. The use of the tool is aimed at maximizing the use of databases current, but also open for use with future databases of new development.